Enacting Entrepreneurship and Leadership: A Longitudinal Exploration of Gendered Identity Work. (28th April 2015) - Lewis, Kate V.; Henry, Colette; Foss, Lene; Fayolle, Alain; Walker, Elizabeth; Duffy, Susan
<x xml:space="preserve">Abstract</x> Entrepreneurship and leadership are enacted as examples of practice and taken on as forms of identity; they are also both understood to be gendered constructions. The paper explores how entrepreneurial leadership is enacted by a female entrepreneur over time and how being a leader is integrated into entrepreneurial identity development via gendered identity work. The empirical foundation of the paper is a longitudinal case study of a New Zealand female entrepreneur that is informed by primary data spanning almost a decade (2005–2014). The data were collected via multiple, in‐depth, narrative interviews and analyzed using the framework of interpretative phenomenological analysis.